Potensi Maritim Indonesia: Analisis Potensi Sumber Daya Alam Natuna - Siti Agnia; Erni Mulyanie (PPPM Polimarin, 2025)
This study aims to analyze the potential of maritime natural resources in the Natuna region as one of Indonesia’s strategic areas. The research was conducted through a literature review method, collecting secondary data from government reports, scientific publications, and official statistics. The findings reveal that Natuna has significant capture fisheries potential with high economic value, although it remains threatened by illegal fishing activities. In the energy sector, Natuna holds large oil and gas reserves, including the development of the Forel and Terubuk fields as well as the Anambas block, which can support national energy security. Coastal ecosystems such as coral reefs, mangroves, and seagrass beds exhibit high biodiversity and play an essential role in ecological balance, yet face pressures from human activities and environmental changes. Meanwhile, renewable energy potential such as offshore wind and ocean wave energy remains underutilized due to limited data and infrastructure. The study concludes that sustainable management of Natuna’s maritime resources requires an integrative approach through strengthened surveillance, improved infrastructure, further research, and local community empowerment to support Indonesia’s food security, energy independence, and environmental sustainability.